Perancangan Setting Level Optimal dan Penentuan Quality Loss Function pada Pembuatan Tegel dengan Metode Taguchi - Dewi Marlina; Eko Pujiyanto; Cucuk Nur Rosyidi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2003)
Taguchi method is one of methodology that used in off-line quality control activity on the product and process design phase. Tile company that made flowers motif tile which have 30 cm long, 30 cm wide and 3.5 cm thickness often found a product that have under company product quality standard. The aim’s of the research are to define the influence factors of quality design, to determine the optimum conditions of control factors so that the product is least sensitive to uncontrollable factors (noise factors) such a wear, aging and ambient conditions and to count quantitative evaluation of quality loss function due to functional variation